Modern sports ethics a reference handbook - Lumpkin, Angela (Contemporary world issues, 2009)
From the Publisher: An examination of both ethical and unethical behaviors in sports designed to help readers analyze the notion that participating in sports builds character. Is it possible to teach lasting values through sports? With coverage that explores the origins of sports, ethical theories as applied to sports, and key moral issues affecting sports throughout history to the present day, Modern Sports Ethics: A Reference Handbook surveys the realm of athletics and its potential as an arena for character development.